(untitled) (Movimenta (ISSN 1984-4298), 2024)
Abstract: Creatine is a supplement used by athletes and physical activity practitioners, however, the adverse effects of this supplement are still the subject of several scientific debates. Objective: To evaluate creatine supplementation associated with high-intensity strength training on kidney and liver biomarkers in rats. Methods: Male Wistar rats (n=24) were divided into four groups: sedentary (S); sedentary + creatine (SC); trained (T); trained + creatine (TC). The creatine groups were supplemented with 0.040g/kg/body weight of creatine. Strength training consisted of vertical jumps in a water tank, 3 days/week, for 8 weeks. Blood and urine samples were collected for renal and/or liver biochemical analysis. The One-way-ANOVA test was used with p< 0.05. Results: Training associated with creatine increased proteinuria in the TC group (16.38 ± 1.94 mg/24h) compared to the SC group (9.58±1.84 mg/24h) (p=0.02). Training, with or without creatine, was effective in increasing plasma lactate concentration in T (61.17 ± 2.7 mg/dL) and TC (82.2 ± 13.1 mg/dL) animals compared to sedentary animals. (40.17 ± 0.65 mg/dL) as well as creatinine and plasma osmolality and GOT. However, the glomerular filtration rate (GFR), plasma and urinary sodium and potassium concentrations, GPT and the GOT/GPT ratio were not altered by strength exercise or creatine. Conclusion: The renal and hepatic changes evidenced appear to be caused by physiological adaptations to physical exercise and/or creatine supplementation, and not by injuries to these organs.